2016
DOI: 10.1021/acs.chemmater.6b02528
|View full text |Cite
|
Sign up to set email alerts
|

Direct Self-Assembly of Conductive Nanorods of Metal–Organic Frameworks into Chemiresistive Devices on Shrinkable Polymer Films

Abstract: Characterization of MOFs and full devices. Comprehensive sensing data and variance (PDF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
196
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(213 citation statements)
references
References 30 publications
13
196
0
Order By: Relevance
“…In 2016, Smith et al reported the direct growth of M 3 (HHTP) 2 films (M = Cu, Ni) onto graphitic electrodes that had been patterned onto polymer films [33]. Consistent with the previously-reported studies, devices fabricated in this manner from Cu 3 (HHTP) 2 displayed a chemiresistive response towards NH 3 vapor, while devices fabricated from Ni 3 (HHTP) 2 did not display an observable response.…”
Section: Mof-based Gas Sensorssupporting
confidence: 64%
“…In 2016, Smith et al reported the direct growth of M 3 (HHTP) 2 films (M = Cu, Ni) onto graphitic electrodes that had been patterned onto polymer films [33]. Consistent with the previously-reported studies, devices fabricated in this manner from Cu 3 (HHTP) 2 displayed a chemiresistive response towards NH 3 vapor, while devices fabricated from Ni 3 (HHTP) 2 did not display an observable response.…”
Section: Mof-based Gas Sensorssupporting
confidence: 64%
“…Among the commonly reported MOF‐based catalysts, the copper‐based hexahydroxytriphenylene Cu 3 (HHTP) 2 , a two‐dimensional (2D) copper‐based MOF that was first reported by Yaghi and co‐workers, shows good electronic conductivity with excellent electrolyte penetration and charge transport and has also attracted considerable interest as an electrode material in supercapacitors and chemiresistive sensors . Cu 3 (HHTP) 2 has a highly ordered structure made up of open copper sites (OCSs) coordinated to two adjacent deprotonated HHTP ligands to form a 2D hexagonal layer, which has allowed its mode of function to be studied relatively easily. However, in comparison with other MOFs, its high cost could limit its direct application.…”
Section: Introductionmentioning
confidence: 75%
“…[1,2] Recently, there are growing interests in design and synthesis of 2D covalent or noncovalent organic materials with in-plane π-conjugation structure. [17][18][19][20][21][22][23][24][25][26][27][28][29] The planar structure of these graphene analogues facilitates the synthesis of benzene-and triphenylene-polyselenols and CPs containing these ligands (relevant results are in preparation). [17][18][19][20][21][22][23][24][25][26][27][28][29] The planar structure of these graphene analogues facilitates the synthesis of benzene-and triphenylene-polyselenols and CPs containing these ligands (relevant results are in preparation).…”
Section: Coordination Polymersmentioning
confidence: 99%
“…The synthesis of protected BHS hexakis(tertbutylseleno)benzene (t-Bu 6 BHS) was reported by Turner and Vaid in 2012. [17][18][19][20][21][22][23][24][25][26][27][28][29] The planar structure of these graphene analogues facilitates the [33] An alternative approach is Lewis acid promoted deprotection protocol.…”
mentioning
confidence: 99%